Virtual Manipulatives: A Tool to Support Access and Achievement With Middle School Students With Disabilities. Issue 1 (March 2020) - Bouck, Emily C.; Mathews, Leslie A.; Peltier, Corey
Manipulatives offer students with disabilities access and support in classrooms. However, it is important for educators to be aware that concrete manipulatives are not the only option. Teachers serving students identified with a disability in the middle grades may consider selecting virtual manipulatives as supplement, complement, or in lieu of concrete manipulatives. In this technology in action, the authors provide information for educators about using virtual manipulatives and how they can be used across different settings, instructional needs, and mathematical content areas for middle school students with disabilities.